AKTIFITAS BELAJAR SISWA PADA PEMBELAJARAN INKUIRI BERBASIS PENDIDIKAN KARAKTER PADA MATERI EVOLUSI - CHARISMA ENDRAWATI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Abstract : The purpose of this study is to describe the activities of students after using inquiry learning resources based on character education in evolution. The device is tested on a limited basis in high school I Kemala Bhayangkari Surabaya by the number of 42 students. Results of the study is that students do an activity to formulate the problem, propose a hypothesis, collect data, test hypotheses, and formulate conclusions on the evolution of matter. Students show character as thorough, honest, curious and appreciate the logical and empirical approach after conducting an inquiry-based learning character education. Keywords: students' learning activities, an inquiry, Character Education and Content Evolution